Differences of Serum Progesterone-Induced Blocking Factor (PIBF) Levels in Pregnant Women with Abortus Imminent and Normal Pregnancy (Study on Pregnancy I Trimester) - Hidayat, Syarief Thaufik; Hidayat, Muhammad Reza (Syntax Literate, 2025)
To determine the difference in serum Progesterone-Induced Blocking Factor (PIBF) levels in first-trimester pregnant women between abortion imminent and normal pregnancy. An analytical observational study with a cross-sectional method involving 54 research subjects consisting of 27 pregnant women with imminent abortion and 27 pregnant women with normal pregnancies. The dependent variable in this study was serum PIBF levels. In the imminent abortion group, PIBF levels had a mean of 59.43 ng/mL with a standard deviation of 9.05 ng/mL, a median value of 58.24 ng/mL with the smallest value of 47.95 ng/mL, and the largest value of 75.82 ng/mL. There was a correlation between gestational age (p<0.001) and PIBF levels with a strong negative correlation level (r= -0.775). In the normal pregnancy group, PIBF levels had a mean of 111.53 ng/mL with a standard deviation of 24.71 ng/mL, a median value of 108.51 ng/mL with the smallest value of 79.88 ng/mL, and the largest value of 191.14 ng/mL. There was a correlation between gestational age (p=0.049) and PIBF levels with a moderately positive correlation level (r=0.361). There was a significant difference in PIBF levels (p<0.001) between the abortion imminent group and the normal pregnancy group. Subjects with PIBF levels <77.85 ng/mL were at risk for imminent abortion than subjects with PIBF levels > 77.85 ng/mL. PIBF levels were significantly lower in the abortion imminent group than in the normal pregnancy group. In the abortion imminent group, an increase in gestational age was moderately correlated with a decrease in PIBF levels.